Genome-wide association study of response to cognitive–behavioural therapy in children with anxiety disorders. (September 2016) - Coleman, Jonathan R. I.; Lester, Kathryn J.; Keers, Robert; Roberts, Susanna; Curtis, Charles; Arendt, Kristian; Bögels, Susan; Cooper, Peter; Creswell, Cathy; Dalgleish, Tim; Hartman, Catharina A.; Heiervang, Einar R.; et al.
Abstract : Background: Anxiety disorders are common, and cognitive–behavioural therapy (CBT) is a first-line treatment. Candidate gene studies have suggested a genetic basis to treatment response, but findings have been inconsistent. Aims: To perform the first genome-wide association study (GWAS) of psychological treatment response in children with anxiety disorders ( n = 980). Method: Presence and severity of anxiety was assessed using semi-structured interview at baseline, on completion of treatment (post-treatment), and 3 to 12 months after treatment completion (follow-up). DNA was genotyped using the Illumina Human Core Exome-12v1.0 array. Linear mixed models were used to test associations between genetic variants and response (change in symptom severity) immediately post-treatment and at 6-month follow-up. Results: No variants passed a genome-wide significance threshold ( P =5×10 –8 ) in either analysis. Four variants met criteria for suggestive significance ( P <5×10 –6 ) in association with response post-treatment, and three variants in the 6-month follow-up analysis. Conclusions: This is the first genome-wide therapygenetic study. It suggests no common variants of very high effect underlie response to CBT. Future investigations should maximise power to detect single-variant and polygenic effects by using larger, more homogeneous cohorts.